Geneologi dan Transformasi Keilmuan Dakwah - Suhartini, Rr; Ahrori, Syaiful (Jurnal Komunikasi Islam, 2019)
This study aims to describe the direction of the development of Da'wah science developed by the Faculty of Da'wah and Communication of UIN Sunan Ampel Surabaya. This research uses a qualitative approach. Data collected through interviews and documentation. Data analysis techniques using the flow model stages. The results showed that the development of da'wah that occurred at the Faculty of Da'wah and Communication of UIN Sunan Ampel Surabaya was carried out through a system approach, which was centered on the study of da'wah elements and represented in the area of interest in the KPI Study Program as the basis for the development of Da'wah science that manifested in the study area at the BKI, MD, and PMI Study Program. However, the development of da'wah scholarship was also developed through other disciplines (interdisciplinary) when studying the phenomenon of da'wah.